2007
DOI: 10.1007/s00415-007-2025-2
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in neuroimmunological diseases

Abstract: Fatigue is a widespread symptom in numerous neuroimmunological diseases like multiple sclerosis (MS), myasthenia gravis, morbus Behcet, neurosarcoidosis, neuroborreliosis or immune vasculitis. This phenomenon is best investigated in MS. The complex mechanisms underlying fatigue in MS are still poorly understood; alterations in immune system activation, central nervous system dysregulation, impaired nerve conduction, and neuroendocrine dysregulation have to be considered. These immune and neural mechanisms may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 26 publications
1
26
0
1
Order By: Relevance
“…Other studies found significant but small relationships using functional neuroimaging techniques [22][23][24][25][26]. Because fatigue often occurs during disease exacerbations and is also reported to be a side effect of disease-modifying medications such as interferon-β, a relationship with autoimmune dysregulation has been suggested [14,27]. However, the results of studies concerning the relationship between MS-related fatigue and pathophysiological mechanisms, including autoimmune and neuroendocrine dysregulation, autonomic system dysfunction, and peripheral muscular mechanisms, are contradictory [28][29][30][31][32][33] (see Kos et al [13] for a review of the biological mechanisms of MS-related fatigue).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies found significant but small relationships using functional neuroimaging techniques [22][23][24][25][26]. Because fatigue often occurs during disease exacerbations and is also reported to be a side effect of disease-modifying medications such as interferon-β, a relationship with autoimmune dysregulation has been suggested [14,27]. However, the results of studies concerning the relationship between MS-related fatigue and pathophysiological mechanisms, including autoimmune and neuroendocrine dysregulation, autonomic system dysfunction, and peripheral muscular mechanisms, are contradictory [28][29][30][31][32][33] (see Kos et al [13] for a review of the biological mechanisms of MS-related fatigue).…”
Section: Introductionmentioning
confidence: 99%
“…The BDI-II is a 21-item self-report measure designed to assess DSM-IV depressive symptomatology in adolescents and adults. It is a revised version of the amended DI [1]. Respondents are asked to rate each of the depression symptoms, ranging from 0 (not present) to 3 (severe), in terms of how they have been feeling during the past two weeks, recording the date of completing the questionnaire.…”
Section: Measurementsmentioning
confidence: 99%
“…Fatigue has been identified in a broad range of neuroimmunological disorders like multiple sclerosis (MS) [1]. Fatigue is considered an important symptom in MS patients because it affects patients' social lives, occupation, overall quality of life, and mood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dies mag dadurch bedingt sein, dass die Fähigkeiten, die für eine unauffällige Gesprächsführung notwendig sind (Sprache, Orientierung, verbalauditive Merkspanne), häufig unbeeinträchtigt sind und daher möglicherweise bestehende kognitive Beeinträchtigungen im "kurzen" Arzt-Patienten-Gespräch nicht auffallen. Es hat sich jedoch gezeigt, dass Gedächtnis-und Aufmerksamkeitsstörungen die Lebensqualität von MS-Patienten in klinisch relevanter Weise beeinflussen [20,21]. So sind MS-Patienten mit kognitiven Beeinträchtigungen häufiger in der routinemäßigen Haushaltsfüh-rung und in der sexuellen Funktionalität beeinträchtigt.…”
unclassified